Bovine sperm HSP-70 molecules: a potential cryo-tolerance marker associated with semen quality and fertility rate - Pardede, Berlin Pandapotan; Kusumawati, Asmarani; Pangestu, Mulyoto; Purwantara, Bambang (Frontiers in Veterinary Science, 2023)
Introduction: Freezability is the ability of sperm to maintain its vitality and quality from various stress during the cryopreservation process, which is very important for the success of fertilization in AI programs. Heat shock proteins (HSPs) are unique proteins induced in response to various stress, including excess reactive oxygen species (ROS) and oxidative damage to intracellular enzymes that can harm cells. This study aims to identify the potential of the HSP-70 molecule at the mRNA and protein level as one of the molecules in sperm that controls tolerance to cryopreservation processes associated with various parameters of semen quality and fertility levels in the field. Methods: The classification of bulls is based on freezability (good freezability/GF and poor freezability/PF), which is obtained from the value of post-thaw viability using the SYBR-14/PI-flow cytometry. Semen quality assessed included sperm motility and kinetics (computer-assisted sperm analyses), plasma membrane integrity (HOS test), acrosome integrity (FITC-PNA), mitochondrial membrane (JC-1), and DNA damage (Halomax kit). The bull fertility rate assessment was analyzed based on the percentage conception rate of each bull derived from data on the success of artificial insemination contained in the Indonesian-integrated National Animal Health Information System (iSIKHNAS). Gene expression levels of HSP-70 bovine sperm were performed using the RT-qPCR method. The protein abundance of HSP-70 bovine sperm was determined using the enzyme immunoassay (EIA) method. Results: Bovine sperm HSP-70 molecules, at the gene and protein level, and the quality of frozen-thawed sperm showed a higher abundance and percentage in GF (P<0.05) than in PF bulls. Significantly (P<0.01) bovine sperm HSP-70 molecules are closely related to the level of fertility, with a high degree of linearity, HSP-70 gene (R2:0.834) and protein (R2:0.891). Furthermore, sperm HSP-70 molecules are correlated (P<0.01) with various parameters of frozen-thawed sperm quality. The overall quality of frozen-thawed sperm is correlated (P<0.01) with the field's fertility level. Conclusions: We may conclude that HSP-70 molecules in bovine sperm at the mRNA and protein level have the potential to be developed as a marker for cryo-tolerance or freezability, which may be utilized as a predictor of fertility and frozen-thawed sperm quality in bulls.